Underlying Methodology for a Thermal Process Monitoring System for Wire and Arc Additive Manufacturing - Daniel Baier; Tobias Weckenmann; Franz Wolf; Andreas Wimmer; Michael F. Zaeh (Journal of Manufacturing and Materials Processing, 2022)
The Wire and Arc Additive Manufacturing (WAAM) process has a high potential for industrial applications in aviation. The interlayer temperatures influence the dimensions and geometric deviations of the part. Monitoring the absolute interlayer temperature values is necessary for quantifying these influences. This paper presents an approach for determining the absolute values of the interlayer temperatures during the process using Ti-6Al-4V. The emissivity and transmittance are determined and calibrated, enabling precise thermographic measuring during the WAAM process. The recorded thermographic data are then compared to signals of thermocouples so that the absolute temperature values can be aligned. The methodology is validated by its transfer to measure the interlayer temperature at different regions of interest. The effect of a heat accumulation using Ti-6Al-4V in WAAM was determined. The methodology enables a reproducible and non-tactile measurement of the interlayer temperature during the WAAM process. The results show that with an interlayer temperature of 200 °C, a heat accumulation occurs within a layer. The heat accumulates in the center of the layer because the free ends of the layer cool down faster than the center of the layer.